The influence of vegetation-generated turbulence on deposition in emergent canopies - Deitrick, Autumn R.; Hovendon, Erin H.; Ralston, David K.; Nepf, Heidi (Frontiers in Marine Science, 2023)
Laboratory experiments measured sediment deposition and turbulent kinetic energy (TKE) in bare and vegetated channels. The model vegetation represented a mangrove pneumatophore canopy. Three solid volume fractions were considered (ϕ= 0.01, 0.02, and 0.04). For the same channel-averaged velocity, the vegetated region had elevated near-bed TKE compared to the bare region. Net deposition in both regions was measured by adding a sediment slurry of 11-micron solid glass spheres to the flume and collecting the deposited sediment from the flume baseboards after a 4-hr experiment. The elevated near-bed TKE in the vegetated region resulted in lower deposition compared to the bare region. A model for deposition probability written in terms of near-bed TKE (TKE model) more accurately predicted the measured deposition than a model based on bed shear stress (τb model). Application of the model to field conditions suggested that, by inhibiting deposition, vegetation-generated TKE facilitates the delivery of sediment farther into the mangrove forest than would be achieved without vegetation-generated TKE.